Hubungan Usia dan Konsumsi Makanan dengan Gejala Tonsilitis Pada Pasien Poli THT RSUD H. Hanafie Muara Bungo - Malahayati Rusli; Miralza Diza; Alda Rizky (Universitas Batam, 2022)
Background: Tonsillitis is the inflammation of the palatine tonsils caused by bacterial infection of class A Streptococcus & B Hemolyticus which the infection spreads through the air, hands and kisses. Epidemiological data of ENT disease in seven provinces in Indonesia in September 2012 showed the prevalence of chronic tonsillitis was the second rank to the acute nasopharyngitis, which was 3.8%. Methods: This study used a cross sectional study design. The sampling technique was accidental sampling with a sample of 37 respondents. The research was carried out on 15-21 November 2021. Univariate analysis is presented in the frequency distribution table and bivariate analysis using Chi-Square test. Results: The characteristics of the respondents were 22 people (59.4%) female and 15 people were male (40.5%). There were 21 people (56.7%) aged 3-20 years old and aged 21-60 years old 16 people (43.3%). Consuming risky foods as many as 20 people (54.1%) and eating non-risk foods as many as 17 people (45.9%). There were 19 people with tonsillitis symptoms (51.3%) and 18 people with no tonsillitis symptoms (48.7%). There was a significant relationship between age and symptoms of tonsillitis (p = 0.03 ; PR = 4.40 (1.09-17.72)), and there was a significant relationship between food consumption and symptoms of tonsillitis (p = 0.01; PR = 5.60 (1.36-23.05)). Conclusion: There was a significant relationship in which age over 20 years would reduce the occurrence of tonsillitis symptoms and consuming low risk food reduce would the occurrence of tonsillitis symptoms at outpatient ENT polyclinic of H. Hanafie Muara Bungo Hospital.